The prosecution of pirates in national courts - Warner, Robin (Emirates lecture series, 2013)
"This paper provides an analysis of the international legal framework for dealing with piracy and its criminalization in national legal systems. It examines some of the key trends emerging from national prosecutions of Somali pirates since the onset of increased piracy incidents off the Horn of Africa and in the Gulf of Aden, and the initiatives taken by the international community to strengthen the capacity of national legal systems in this region to investigate and prosecute piracy offenses."--Introduction.